The interdependence between the choice of fixed-term professional workers and the control environment - Nair, Sujay; Abernethy, Margaret A.; Jiang, Yile (Anson); Lillis, Anne M. (Accounting, Organizations and Society, 2024)
Many organizations have professional employees on fixed-term and ongoing employment contracts. While hiring employees on fixed-term contracts offers organizations operational flexibility and other benefits, it also brings about challenges in the form of relatively lower goal alignment and ability of these employees, thus creating the need for management controls. At the same time, given the costs and constraints of designing and implementing a control system, we expect that the planned use of fixed-term workers would be affected by the type of control environment that organizations are willing or able to create. Hence, this study investigates whether an organization's choice of its control environment and its use of fixed-term professional employees are interdependent (i.e., made jointly). Using surveys from different sources and archival data from the education sector, we find that some types of controls (i.e., action controls and organizational culture) and the organization's choice of using fixed-term employees are interdependent, while other controls (i.e., employee selection practices and results control) are independent of this choice. We also find that the interdependence between the choice of using fixed-term employees and the control environment is generally weaker when organizations use fixed-term contracts as an implicit screening mechanism for ongoing employment. Finally, in additional analysis, we find evidence that the interdependence between controls and the use of fixed-term employees is primarily due to concerns related to goal alignment rather than ability.